Intergenerational influence: the pathway to radicalisation - Rahmah, Unaesah (2023)
In January 2023, Askary Sibghotulhaq, the son of former Jemaah Islamiyah leader Parawijayanto, appeared in court on charges of facilitating the departure of members of the banned group for military training in Syria. Analysts had anticipated that Askary would be his father’s successor as the next JI leader because of his religious knowledge, military training, and kinship networks. His case highlights the prevalence of intergenerational radicalisation within Indonesian terrorist networks.